Why Othering should be considered in research on health inequalities: Theoretical perspectives and research needs - Nurcan Akbulut; Oliver Razum (SSM: Population Health, 2022)
Othering broadly refers to various constructed notions of (non-)belonging and difference that engender marginality and structural inequality. Social-psychological approaches that conceive ingroup and outgroup formations as an interaction between cognitive, emotional, and conative processes are not sufficient to conceptualize Othering. It is important to include the social and historical imprint of Othering and the resulting power relations between ingroups and outgroups. In this paper we demonstrate that a postcolonial-intersectional perspective is needed to understand the social and discursive character of Othering and the historically grown formation of Self-Other power relations. Othering can be understood as a (multidimensional) social phenomenon that requires a critical perspective on difference to analyze the processes of making Others through difference construction.Othering is relevant to public health as an analytical lens that helps to understand the link between minority status and health inequalities. Othering can affect health in different ways as it occurs in multiple dimensions and forms that vary according to marginalized groups and institutional as well as social contexts. First, Othering can affect othered persons on an individual level. Second, Othering can manifest itself at the institutional level of health care institutions; and third, it can have far-reaching effects on a contextual level. To benefit from the analytical capacity of this concept, and to understand the complex relationship between Othering and health, a theoretical understanding of Othering is needed.